2023
DOI: 10.1002/jaba.978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating caregivers arrangement of infant sleeping environments in the home

Abstract: Sleep‐related infant deaths are one of the top causes of infant mortality in the United States. A few behavior analytic studies have examined behavioral skills training to teach adults to arrange safe infant sleeping environments. These studies were conducted in an analogue environment, and no data were collected outside the training setting. The purpose of the current study was to replicate and extend the extant literature. We taught caregivers to arrange safe infant sleeping environments in a community‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Sleep‐related infant deaths have remained stable for the past few decades (Centers for Disease Control and Prevention, 2022), prompting additional research on how to train caregivers in arranging safe sleep environments. A growing number of studies have shown the effectiveness of BST to train adults to engage in safe infant sleeping practices (Carrow et al, 2020; Mery et al, 2022; Mery et al, 2023; Vladescu et al, 2020), thereby demonstrating the efficacy of the training protocol developed by Carrow et al (2020) and Vladescu et al (2020). Interestingly, we found outcomes similar to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sleep‐related infant deaths have remained stable for the past few decades (Centers for Disease Control and Prevention, 2022), prompting additional research on how to train caregivers in arranging safe sleep environments. A growing number of studies have shown the effectiveness of BST to train adults to engage in safe infant sleeping practices (Carrow et al, 2020; Mery et al, 2022; Mery et al, 2023; Vladescu et al, 2020), thereby demonstrating the efficacy of the training protocol developed by Carrow et al (2020) and Vladescu et al (2020). Interestingly, we found outcomes similar to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated behavioral skills training (BST; DiGennaro Reed et al, 2018) to teach college students (Carrow et al, 2020), expectant caregivers (Mery et al, 2023;Vladescu et al, 2020), and medical students (Mery et al, 2022) to arrange an analogue infant sleeping environment that corresponded with the recommendations of the American Academy of Pediatrics (Moon et al, 2022a(Moon et al, , 2022b. In all studies, participants responded with low to moderate levels of correct responding across scored safe-sleeping categories (i.e., surface, materials, position) during baseline measures, and they subsequently reached the mastery criterion following the implementation of BST.…”
mentioning
confidence: 99%
See 3 more Smart Citations